Applying imaging mass spectrometry to define the N-glycan profiles of co-localized virus and immune cell infiltrates in post-COVID-19 infected lung autopsy tissues - Jones, E. Ellen; Drake, Richard R.; Dressman, James W.; Parihar, Vaunita; Stubler, Rachel; Masters, Elysia; Mercer, Kelly E. (Frontiers in Analytical Science, 2022)
The current COVID-19 pandemic is characterized by a broad range of disease severity in patients. This kind of diversity in clinical manifestations has complicated our understanding of the virus and highlights the significance of an individual’s ability to mount an effective viral immune response in relation to morbidity. Glycosylation is a common post translational modification occurring in complex organisms and imperative for immune cell function. In this study, a combination approach with immunohistochemistry (IHC) and Matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI-IMS) was utilized to determine the spatial distribution of N-glycans and with different immune cell populations in COVID-19 lung tissues. Tissues from 7 SARS-CoV-2, PCR+ donors were analyzed. Tissues represented a spectrum of time spent on ventilators which was reflected in their respective viral infection status and lung pathologies. N-glycan distributions in the MALDI-IMS images were then correlated with H&E staining and IHC of SARS-CoV-2 spike protein, CD4, CD8, CD163 and CD11b. Distinct and shared N-glycan signatures were identified in association with specific immune cell types, and their co-localization with the viral spike protein. Additionally, we observed unique patterns of a2,3-linked and a2,6-linked sialic acid glycans that associated with both immune cell populations and fibrotic regions within the tissue architecture. N-glycan MALDI-IMS is an effective tool to further understand tissue localized immune cell populations in response to emerging viral pathogens such as COVID-19.